Case report: An unusual presentation of intra-abdominal desmoplastic small round cell tumor - Desai, Akshay Nilesh; Kurian, Christine Jane; Rafferty, William; Behrens, Danielle Lajoie; Khrizman, Polina (Frontiers in Oncology, 2024)
Background Intra-abdominal desmoplastic small round cell tumor (IDSRCT) is a rare entity (0.2–0.74 cases per million people per year), which predominantly occurs in young men. It may present as an abdominal mass with pain, distention, and constipation. IDSRCT has a very poor prognosis, with 5-year overall survival estimated at 15%–30%. Diagnosis is made with tissue biopsy. Case description We present a case of a 28-year-old man with a history of schizophrenia and depression who presented to an emergency room (ER) in November 2022 with constipation and pelvic pain. The patient was sent home with a bowel regimen after radiography showed no obstruction. He re-presented for evaluation due to persistent pain. A computerized tomography scan of the abdomen and pelvis (CT A/P) revealed numerous pelvic masses with severe colitis, bilateral moderate hydronephrosis, and metastatic disease in the liver. A colonoscopy showed a mass extending 3 cm from the anus to 10 cm causing a partial obstruction. Biopsy was read as squamous cell carcinoma (SCC). The patient was subsequently admitted to our institution with pelvic pain, nausea, and vomiting. Colorectal surgery performed a colectomy with end-ileostomy due to colonic obstruction. He was evaluated by a medical oncologist, with previous slides requested for review. Initial review was concerning metastatic basaloid SCC with neuroendocrine features and a Ki67 of 70%. Given his recent abdominal surgeries, chemotherapy was delayed until February 2023 when he was started on reduced dose carboplatin and paclitaxel. Tumor specimen was sent for next generation sequencing (NGS) and programmed death-1 ligand 1 (PD-L1) testing. NGS results returned after the first dose of chemotherapy was given and showed a t(11;22) EWSR-WT1 translocation characteristic of desmoplastic small round cell tumor. The patient was supported in the hospital and discharged with oncology follow-up. Discussion As seen in this case, pathology review is essential to ensuring correct diagnosis and appropriate treatment plan. This is especially true when the clinical scenario does not match the listed pathology. Additional diagnostics such as NGS are invaluable in establishing correct diagnosis.